Unusual Clinical and Pathological Features in Pemphigus Vulgaris: A Potential Diagnostic Pitfall - Rosario Caltabiano; Gaetano Magro; Lidia Puzzo; Enrico Vasquez; Rocco De Pasquale (Case Reports in Medicine)
We describe the case of a 67-year-old woman affected by pemphigus vulgaris with a dry whitish scaly lesion in the upper lip. Clinically, this lesion resembled an actinic keratosis. Although histological examination revealed a focal acantholysis, the finding of a moderate-to-severe dysplastic epithelium was consistent with the diagnosis of acantholytic actinic keratosis with moderate/severe dysplasia. Nevertheless, the complete resolution of the lip lesion after systemic therapy for pemphigus vulgaris led us to reconsider the possibility that we were dealing with a pemphigus vulgaris with unusual clinical and histological features. The previously reported cytological dysplasia was better regarded reactive rather than neoplastic, likely as the result to the inflammatory injury.